2019
DOI: 10.1021/acs.jpcc.9b09033
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Photophysical and Nonlinear Properties in Conformation Isomerization of Macrocyclic [32]Octaphyrin(1.0.1.0.1.0.1.0) Involving Hückel and Möbius Topologies

Abstract: The conversions of photophysical and nonlinear optical (NLO) properties in [32]octaphyrins(1.0.1.0.1.0.1.0) following macrocyclic isomerization between Huckel and Mobius topologies have been studied in detail by means of quantum chemistry calculations. Compared to their quasi-planar analogues, the twisted Mobius and the figure-eight Huckel conformers exhibit red-and blue-shifted absorptions, respectively. The fluorescence emissions of Huckel topological molecules are likely to be from the second excited state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 55 publications
2
38
1
Order By: Relevance
“…There is no significant difference between the α iso of Li@C 18 in and Li@C 18 out , which is similar to the law of polarizability between the analogues of many other types of compounds we have studied [41][42][43][44]. However, the change in the way of binding of Li atom not only causes the magnitude of β vec to vary, but also alters the sign of it.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexessupporting
confidence: 67%
See 1 more Smart Citation
“…There is no significant difference between the α iso of Li@C 18 in and Li@C 18 out , which is similar to the law of polarizability between the analogues of many other types of compounds we have studied [41][42][43][44]. However, the change in the way of binding of Li atom not only causes the magnitude of β vec to vary, but also alters the sign of it.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexessupporting
confidence: 67%
“…The (hyper)polarizability density analysis, which graphically exhibits the spatial contribution of electrons in a molecule to electric response properties, is helpful to gain a deep insight into the physical nature of molecular (hyper)polarizability [17,[41][42][43][44]. The (hyper)polarizability densities, namely the local contributions to the respectively, for comparison.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexesmentioning
confidence: 99%
“…However, C 10 shows a distinctive difference with significantly large gap. The HOMO‐LUMO gap of a molecular ring has a close relationship with its aromaticity, [30] and it is notable that the aromaticity of C 10 as distinct from that of other carbon rings has been reported, [18] and some works have revealed that molecular aromaticity can serve as a fingerprint of optical properties in organic macrocycles [31–33] . With these facts in mind, the large gap of C 10 is not unexpected.…”
Section: Methodsmentioning
confidence: 92%
“…However, C10 shows a distinctive difference with significantly large gap. It is notable that the aromaticity of C10 as distinct from that of other carbon rings has been reported [18], and some works have revealed that molecular aromaticity can serve as a fingerprint of optical properties in organic macrocycles [40][41][42], which jointly explain its anomaly. Oscillator strength (f) of an excited state is proportional to the square of transition dipole moment (μ T ) corresponding to this state, while transition dipole moment density is able to intuitively reveal the contribution of different spatial positions to μ T [43].…”
Section: Photophysical Property Of C2n Allotropesmentioning
confidence: 99%